Kinetics of surfactin production by bacillus subtilis in a 5 L Stirred-tank Bioreactor - Muhammad Qadri Effendy Mubarak; Mohd Hafez Mohd Isa; Jufri S.H.M.; Zahar S.M.S.N.S.; Kalil M.S.; Hamid A.A. (Penerbit Universiti Kebangsaan Malaysia, 2024)
Indexed by SCOPUS